SURVEI KEPUASAN STAKEHOLDERS TERHADAP KINERJA ALUMNI INSTITUT PEMERINTAHAN DALAM NEGERI - Agus Supriadi Harahap (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2019)
Institut Pemerintahan Dalam Negeri (IPDN) is the university educating the candidates of leaders in local government institutions. Performance of its alumnus will be an important factor for the success of implementation of government tasks. This study aims to measure the performance of IPDN’s alumnus and the satisfaction of the stakeholders to the aforementioned performance. Data were collected through survey in thirteen provinces, and were analyzed through techniques of statistical descriptive and gap analysis. Among the eight selected dimensions of performance, namely communication skills, organizational skills, leadership, logic, effort, group skills, ethics, and other, it is found that the biggest gaps exist in the dimension of organizational skills and ethics. These findings indicate that IPDN needs to focus to development of the two dimension in itseducational process. Keywords: Employee performance; High education of Kepamongprajaan; Stakeholder’s satisfaction